EVALUASI PROGRAM IMPLEMENTASI PENDEKATAN BEYOND CENTERS AND CIRCLE TIME (BCCT) - OKTARIA, RENTI (JPUD - Jurnal Pendidikan Usia Dini, 2014)
Abstract: The evaluation research aimed to acknowledging the effectiveness ofthe implementation of beyond centers and circle time approach at RA Istiqlal Jakarta Pusat in 2014. The evaluation research is selected as a research method, use the CIPP Model from Daniel Stufflebeam. The research were use multi technique and instrumen to collect the data and analizying data use the desciptive statistic and qualitative technique. The result of research give a conclusion that the implementation of beyond centers and circle time approach at RA Istiqlal Jakarta Pusat in 2014 has been effective. It was seem that (1) RA Istiqlal Jakarta has been the curriculum and handbook of beyond centers and circle time; (2) There are 20 teachers average graduation of S-1 and they received basic training of BCCT and communication skill; (3) There are 10 centers consist of ibadah, natural materials, macro dramatic play, micro dramatic play, block, readiness, movement, creative art, music, and cooking; (4) Child classified by age group with a ratio 12 2 that 12 students with 2 teachers; (5) Teacher have implemented scaffolding the environment, scaffolding the pre-play experience, scaffolding the individual child’s play experience, and scaffolding the post play experience; (6) High quality play environments for children support the three kinds ofplay. Keywords:Evaluation Program, Beyond Centers and Circle Time,Early Childhood Education. Abstrak: Studi evaluasi ini bertujuan untuk mengetahui efektivitas dari pelaksanaan pendekatan beyond centers and circle time(BCCT) di RA Istiqlal Jakarta Pusat tahun 201 4. Metode penelitian yang digunakan adalah evaluasi dengan model CIPP dari Daniel Stufflebeam. Teknik pengumpulan data menggunakan observasi, wawancara, dan angket.Analisis data menggunakan deskripsi. Hasil penelitian adalah implementasi pendekatan BCCT di RA Istiqlal Jakarta tahun 201 4 berjalan efektif, yakni: (1 ) RA Istiqlal Jakarta memiliki kurikulum dan panduan BCCT; (2) Ada 20 orang guru lulusan S1 dan mendapatkan pelatihan dasar BCCT dan keterampilan komunikasi; (3) Ada 1 0 sentra yang terdiri dari sentra ibadah, bahan alam, main peran makro, main peran mikro, balok, persiapan, olah tubuh, seni kreativitas, musik dan memasak; (4) Murid diklasifikasi berdasarkan kelompok usia dengan rasio 1 2 orang anak dengan 2 orang guru; (5) Guru telah melaksanakan pijakan penataan lingkungan, pijakan pengalaman sebelum main, pijakan pengalaman main setiap anak, dan pijakan pengalaman setelah main; dan (6) 3 jenis main didukung dengan adanya lingkungan main yang berkualitas untuk murid. Kata kunci: Evaluasi Program, Beyond Centers and Circle Time, PAUD.